Analysis of Providing Legal Assistance to Vulnerable Groups in Wonogiri Regency: Analisis Pemberian Bantuan Hukum Kepada Kelompok Rentan Di Kabupaten Wonogiri - Widhi Nugroho, Aziz; Eko Mardani, Retno; Fatimah, Siti; Rizki Ruswandi, Melia (Fakultas Hukum Universitas Jambi, 2024)
Wonogiri Regency already has a good commitment through the draft Regional Regulation initiative which specifically guarantees the implementation of citizens' constitutional rights regarding the provision of legal aid for the poor and vulnerable groups. So far, the provision of legal aid has focused on poor people, but now with the expansion of the subject, it really helps other cases in society, so their inability to realize their constitutional rights has been helped. Preparation of research related to the Implementation of Wonogiri Regency Regional Regulations concerning the Provision of Legal Aid for the Poor was carried out using a constructivist paradigm and a qualitative approach where the focus of this study was to understand and develop the meaning of a social phenomenon that was occurring so that it could be understood by first collecting views. participants in the situation being studied. The reflection of the principle of equality before the law in the implementation of the Wonogiri Regency Regional Regulation concerning the Provision of Legal Aid for the Poor cannot yet be measured because the implementation of this Regional Regulation has not been optimal, this is due to the lack of budget allocation for collaborating with Legal Aid Providers, both Legal Aid Organizations and Legal Aid Institute.